(untitled) (शोधसुधा Shodh Sudha, 2023)
Yakthung Limbu have, from time immemorial, a tradition of narrating or reciting Mundhums and performing rituals and ceremonies in their own distinctive ways. The Mundhum is an ancient religious scripture and folk literature of the Limbu. This article attempts to examine how Mundhum performances hold widespread social and cultural significance in Limbu community. Utilizing the perspective of performance culture as theoretical approach, the article illustrates how the narratives and ritual performances of the Mundhum set the ideas to meet wider cultural and religious necessities of the Limbu community - providing them with an insight into understanding the common spirit of the community, and creating an occasion of social solidarity, reconciliation, moral and psychological purification and also an occasion for correcting themselves from any deviation.